Time-course gait pattern analysis in a rat model of foot drop induced by ventral root avulsion injury - Chan, Shu-Yen; Kuo, Chi-Wei; Liao, Tsai-Tsen; Peng, Chih-Wei; Hsieh, Tsung-Hsun; Chang, Ming-Yuan (Frontiers in Human Neuroscience, 2022)
Foot drop is a common clinical gait impairment characterized by the inability to raise the foot or toes during walking due to the weakness of dorsiflexors of the foot. Lumbar spine disorders are common neurogenic causes of foot drop. The accurate prognosis and treatment protocols of foot drop are not well delineated in the scientific literature due to the heterogeneity of the underlying lumbar spine disorders, different severities and distinct definitions of the disease. For translational purposes, the use of animal disease models could be the best way to investigate the pathogenesis of foot drop and help develop effective therapeutic strategies for foot drops. However, no relevant and reproducible foot drop animal models with a suitable gait analysis method were developed for the observation of foot drop symptoms. Therefore, the present study aimed to develop a ventral root avulsion (VRA)-induced foot drop rat model and record detailed time-course changes of gait pattern following L5, L6 or L5 + L6 VRA surgery. Our results suggested that L5 + L6 VRA rats exhibited changes in gait patterns, as compared to sham lesion rats, including a significant reduction of walking speed, step length, toe spread and swing phase time, as well as an increased duration of the stance phase time. The ankle kinematic data exhibited that the ankle joint angle increased during the mid-swing stage, indicating a significant foot drop pattern during locomotion. Time-course observations displayed that these gait impairments occurred as early as the first-day post-lesion and gradually recovered 7 to 14 days post-injury. We conclude that the proposed foot drop rat model with a video-based gait analysis approach can precisely detect the foot drop pattern induced by VRA in rats, which can provide insight into the compensatory changes and recovery in gait patterns and might be useful for serving as a translational platform bridging human and animal studies for developing novel therapeutic strategies for foot drop.